Perbedaan Serum Glutamic Pyruvic Transaminase dan Kreatinin pada Preeklampsia Berat Early Onset dengan Late Onset - Rayhana Yamini; Bambang Abimanyu; Azma Rosida (Homeostasis, 2020)
Abstract: Severe preeclampsia is one of hypertension in pregnancy that is accompanied by proteinuria or involvement of other organs, such as liver and kidney which can be seen from the increased activity of Serum Glutamic Pyruvic Transaminase (SGPT) of the liver and renal creatinine levels. Severe preeclampsia is distinguished by early onset and late onset. The purpose of this study was to determine the differences between SGPT and creatinine in severe early onset preeclampsia with late onset in Ulin Hospital Banjarmasin from January to December 2018. The study was analytic observational. Samples were taken with a non-probability sampling technique with a purposive sampling method, obtained 210 samples that fit the inclusion and exclusion criteria from secondary data. Data analysis using the Mann-Whitney test. The results showed that the median and percentile SGPT of early onset were 28.60 (8-571) U/L and late onset were 20.00 (4-611) U/L. The median and percentile creatinine of early onset were 0.91 (0.45-2.97) mg/dL and late onset were 0.72 (0.19-2.46) mg/dL in severe preeclampsia. There was a significant difference (p = 0.007) in SGPT and (p = 0.002) in creatinine in early onset severe preeclampsia with late onset in Ulin Hospital Banjarmasin in the January-December 2018 period. Keywords: SGPT, creatinine, severe preeclampsia, early onset, late onset. Abstrak: Preeklampsia berat adalah salah satu hipertensi pada kehamilan yang disertai proteinuria atau keterlibatan organ lain, seperti hati dan ginjal yang dapat dilihat dari peningkatan aktivitas Serum Glutamic Pyruvic Transaminase (SGPT) hati dan kadar kreatinin ginjal. Preeklampsia berat berdasarkan awitan dibagi menjadi early onset dan late onset. Tujuan penelitian untuk mengetahui perbedaan SGPT dan kreatinin pada preeklampsia berat early onset dengan late onset di RSUD Ulin Banjarmasin periode Januari-Desember 2018. Penelitian bersifat observasional analitik. Sampel diambil dengan teknik non-probability sampling dengan metode purposive sampling, didapatkan 210 sampel yang sesuai dengan kriteria inklusi dan eksklusi data diambil dari data sekunder. Analisis data menggunakan uji Mann-Whitney. Hasil penelitian didapatkan median SGPT early onset sebesar 28,60 U/L dengan nilai minimum-maksimum 8-571 U/L, median SGPT late onset sebesar 20,00 U/L dengan nilai minimum-maksimum 4-611 U/L, median kreatinin early onset sebesar 0,91 mg/dL dengan nilai minimum-maksimum 0,45-2,97 mg/dL, median kreatinin late onset sebesar 0,72 mg/dL dengan nilai minimum-maksimum 0,19-2,46 mg/dL pada preeklampsia berat. Terdapat perbedaan bermakna (p = 0,007) pada SGPT dan (p = 0,002) pada kreatinin preeklampsia berat early onset dengan late onset di RSUD Ulin Banjarmasin periode Januari-Desember 2018. Kata-kata kunci: SGPT, kreatinin, preeklampsia berat, early onset, late onset.